2020
DOI: 10.1002/adom.201902022
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Quantum Dots with Ionic Liquid: A Multifunctional White Light Emitting Hydrogel for Enzyme Packaging

Abstract: Herein, a new and straightforward approach for the fabrication of a stable and multifunctional white light emitting (WLE) hydrogel is reported. For the first time, the utility of such hydrogels for protein packaging with enhanced activity and stability is presented. Initially, a WLE composite with color chromaticity of (0.33, 0.27) is fabricated by engineering the surface of an orange light emitting Mn2+‐doped ZnS quantum dot (QD) using a blue‐emitting choline‐tosylate ionic liquid (IL). The color chromaticity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…It is noteworthy that the amide carbonyl stretching mode appears at 1680 cm −1 , C–O–C peak at 1215 cm −1 , the esteric C-O stretching at 1172 cm −1 , and C–O stretching vibrations at 1050 cm −1 18 . It can also be observed that there are bands in the range of about 1180 and 1384 cm −1 , which are due to the C–N stretching vibration and methylene group deformation vibrations from SA and [APMim][Cl] 19 , 20 . The bands at 2854, 2920 and 1452 cm −1 also reveal the symmetric, asymmetric stretching, and scissoring vibration modes from –CH 2 groups of these two moieties 21 .…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that the amide carbonyl stretching mode appears at 1680 cm −1 , C–O–C peak at 1215 cm −1 , the esteric C-O stretching at 1172 cm −1 , and C–O stretching vibrations at 1050 cm −1 18 . It can also be observed that there are bands in the range of about 1180 and 1384 cm −1 , which are due to the C–N stretching vibration and methylene group deformation vibrations from SA and [APMim][Cl] 19 , 20 . The bands at 2854, 2920 and 1452 cm −1 also reveal the symmetric, asymmetric stretching, and scissoring vibration modes from –CH 2 groups of these two moieties 21 .…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16] The details of the fabrication of ligand-free Mn 2+ -doped ZnS QDs and the technique of sensing of VB12 are described in the ESI. † 19 The as-fabricated Mn 2+ -doped ZnS QDs exhibited an absorption edge at 310 nm and an intense emission peak at 587 nm (due to the 4 T 1 -6 A 1 electronic transition of the Mn 2+ dopant ions present in the ZnS host) [17][18][19][20][21][22][23] at an excitation wavelength of 320 nm (Fig. 1A and B).…”
mentioning
confidence: 99%
“…Environmentally sustainable metal-based QDs, especially Mn 2+ -doped ZnS QDs, have demonstrated their usefulness in bioimaging, white light generation, light emitting devices and optical sensing due to their long-wavelength atomic orange-red emission, photostable nature and lower toxicity. [17][18][19][20][21][22][23] For example, (i) white light generation could be possible from Mn 2+doped ZnS QDs followed by complexing their surface with two luminescent inorganic complexes, (ii) a reversible pH nanoprobe (in the physiological range 6.5-10.6) can be fabricated by complexing the surface of Mn 2+ -doped ZnS QDs with external chelating ligands, (iii) a white light emitting hydrogel, with the capability of enzyme packaging, could also be fabricated followed by engineering of the surface of Mn 2+ -doped ZnS QDs with ionic liquids. [19][20][21] Thus, the biocompatibility, ease of aqueous-based fabrication and lower toxicity of Mn 2+ -doped ZnS QDs make them a prime choice for the luminescence-based sensitive and selective detection of VB12.…”
mentioning
confidence: 99%
See 2 more Smart Citations